HOPE AND UTOPIA IN POST-TRUTH TIMES: A FREIREAN APPROACH ESPERANÇA E UTOPIA EM TEMPOS DE PÓS-VERDADE: UMA ABORDAGEM FREIREANA - Bernadette Farrell; María Carolina Nieto Ángel; Mônica Maciel Vahl (Revista Brasileira de Alfabetização, 2018)
This article discusses the concept of post-truth based on the work and ideas of Paulo Freire. After 20 years, Freire's legacy continues to urge us to become aware of the ethical, political and educational implications of subtle forms of oppression that have contempt for the truth. Considering the current post-truth context, this text grapples with the following questions: How is it that society gets to the point of “normalising wilful disregard” for facts and evidence? What is the role of education? Is it still possible, given the increasing amounts of intolerance around the world, to dream of a fairer and more humane society? This article explores these questions in the form of a dialogue, where the voices of the three researchers engage from multicultural and interdisciplinary perspectives.